VD_FINDINFO Faillite / 2024 / 23 vom 11. September 2024 - VD Tribunal cantonal (2024)
PROVISOIRE, SURSIS CONCORDATAIRE, PROLONGATION, DÉCISION NÉGATIVE, OUVERTURE DE LA FAILLITE | 293a al. 1 LP, 293a al. 3 LP, 295c al. 1 LP